Bacteriological assessment of pig carcass sites during the slaughtering process - Kadam, A B; Waskar, V S; Paturkar, A M; Zende, R J (The Indian Journal of Animal Sciences, 2005)
Swab samples of pig carcass sites collected from slaughtered animals were analysed for pathogenic and spoilage organisms. Amongst slaughter operations, sticking showed maximum counts followed by transportation, retailing and evisceration operations and were considered to be the critical operations. Amongst the carcass sites jowl and rump showed maximum contamination irrespective of the operations. The prevalence ofthe various pathogenic and spoilage organisms varied throughout the operations.